2017
DOI: 10.3168/jds.2017-12718
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substituting soybean meal and canola cake with dried distillers grains with solubles at 2 dietary crude protein levels on feed intake, milk production, and milk quality in dairy cows

Abstract: Dried distillers grain with solubles (DDGS) is an alternative source of feed protein for dairy cows. Previous studies found that DDGS, based on grains other than corn, can substitute for soybean meal and canola cake as a dietary protein source without reducing milk production or quality. As societal concerns exist, and in many areas strict regulation, regarding nitrogen excretion from dairy cows, the dairy industry has focused on reducing dietary protein level and nitrogen excretion. In the present study, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
4
6
0
Order By: Relevance
“…The content of saturated FAs with less than 16 carbons were linearly reduced with increased DDGS proportion in the ewe diets, while the only saturated FA that came close to increase was C18:0 and this difference was not significant. These results are in line with those of a previous study in ewes (Cais-Sokolińska et al, 2015) and with many studies conducted in cows (Leonardi et al, 2005;Anderson et al, 2006;Sasikala-Appukuttan et al, 2008;Abdelqader et al, 2009;Hippen et al, 2010;Kurokawa et al, 2013;Gaillard et al, 2017aGaillard et al, , 2017b showing diminished de novo FA percentages and increased levels of long-chain FA (LCFA) as a result of DDGS dietary inclusion. The reduction of SFA in the present study was accompanied by a linear increase in total PUFA and MUFA with the increasing concentrations of DDGS in the a-c Means within a row not sharing a common superscript differ due to the different diet examined (P < 0.05), 1 Probability of significant effects due to diet (D), time (T), and their interaction (D × T); *P < 0.05; **P < 0.01; ***P < 0.001, NS, Non-significant; †P < 0.1: tendency, 2 Other C18:1 cis = C18:1 cis-11; C18:1 cis-12; C18:1 cis-13; C18:1 cis-14; C18:1 cis-15, 3 SCFA = short-chain fatty acids (C4:0 to C8:0), 4 MCFA = medium-chain fatty acids (C10:0 to C16:1), 5 LCFA = long-chain fatty acids (C17:0 and above), 6 Atherogenic index = (C12:0 + 4 × C14:0 + C16:0)/(ΣMUFA + ΣPUFA),…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The content of saturated FAs with less than 16 carbons were linearly reduced with increased DDGS proportion in the ewe diets, while the only saturated FA that came close to increase was C18:0 and this difference was not significant. These results are in line with those of a previous study in ewes (Cais-Sokolińska et al, 2015) and with many studies conducted in cows (Leonardi et al, 2005;Anderson et al, 2006;Sasikala-Appukuttan et al, 2008;Abdelqader et al, 2009;Hippen et al, 2010;Kurokawa et al, 2013;Gaillard et al, 2017aGaillard et al, , 2017b showing diminished de novo FA percentages and increased levels of long-chain FA (LCFA) as a result of DDGS dietary inclusion. The reduction of SFA in the present study was accompanied by a linear increase in total PUFA and MUFA with the increasing concentrations of DDGS in the a-c Means within a row not sharing a common superscript differ due to the different diet examined (P < 0.05), 1 Probability of significant effects due to diet (D), time (T), and their interaction (D × T); *P < 0.05; **P < 0.01; ***P < 0.001, NS, Non-significant; †P < 0.1: tendency, 2 Other C18:1 cis = C18:1 cis-11; C18:1 cis-12; C18:1 cis-13; C18:1 cis-14; C18:1 cis-15, 3 SCFA = short-chain fatty acids (C4:0 to C8:0), 4 MCFA = medium-chain fatty acids (C10:0 to C16:1), 5 LCFA = long-chain fatty acids (C17:0 and above), 6 Atherogenic index = (C12:0 + 4 × C14:0 + C16:0)/(ΣMUFA + ΣPUFA),…”
Section: Resultssupporting
confidence: 92%
“…Small increases (not always significant) have also been reported in some studies with lactating cows (Janicek et al, 2008;Chibisa et al, 2012;Benchaar et al, 2013) and it has been attributed to either the slightly increased energy density, due to higher fat content in DDGS diets, or to greater DM intake and, therefore, higher energy acquisition by the animals offered DDGS. Nevertheless, most cow studies with isoenergetic and isonitrogenous experimental diets, and similar intakes, as those applied in the present experiment, reported no effect on milk yield, when the applied inclusion level of DDGS was up to 30% DM (Abdelqader et al, 2009;Gaillard et al, 2017aGaillard et al, , 2017bTestroet et al, 2018) DDGS inclusion did not affect milk protein levels in the present study (Table 1), a fact that was also reported in a previous related study in sheep (Alshdaifat and Obeidat, 2019). Nonetheless, the results in previous studies with cows on the effect of DDGS on milk protein content are controversial, reporting either an increase (Testroet et al, 2015), or a decrease (Kleinschmit et al, 2006;Benchaar et al, 2013;Kurokawa et al, 2013), or no significant effect (Anderson et al, 2006;Janicek et al, 2008;Sasikala-Appukuttan et al, 2008;Chibisa et al, 2012).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Shingfield et al [ 96 ] did not find any differences in pasteurized milk derived from grass (timothy and meadow fescue) silages with or without additives (formic acid, orthophosphoric acid and Enzymax) and hay (timothy and meadow fescue) using a trained descriptive panel ( Table 3 ). Gaillard et al [ 97 ] evaluated the impact of different protein concentrations (14% and 16%) in feed using different sources of protein (soybean meal canola caked and died distiller’s grains with solubles) on pasteurized milk quality. Using descriptive sensory analysis with a trained panel they found no significant sensory difference ( Table 3 ).…”
Section: Sensory Perception Of Pasteurized Bovine Milkmentioning
confidence: 99%
“…As feeds become more expensive and unavailable, and ethanol becomes more abundant and cheap, the use of DDGS as an alternative feed becomes more popular because of price. Dried distillers grains with solubles are rich in fibre, protein and fat and can be fed as a protein source (Gaillard et al 2017; B€ ottger and S€ udekum 2018) when fed at <150 gkg À1 DM or as an energy source when included at levels greater than 150 gkg À1 DM in ruminant diets (Klopfenstein et al 2008). It contains high levels of energy (3.67-4.34 Mcal/kg of DM) and fat (Engel et al 2008) in addition to being highly digestible, making it the most economical feed components for animals (Pecka-Kiełb et al 2015).…”
Section: Introductionmentioning
confidence: 99%